Growth and Yield Performance of Irrigated Lowland Rice NSIC Rc218 (Oryza sativa L.) as Influenced by Water and Fertilizer Applications - Cagasan, Ulysses A.; Tamayo, Nemisio V. (Annals of Tropical Research, 2016)
For better rice productivity there is a need to address the problems on water shortage and nutrient management. This study was conducted to evaluate the growth and yield performance and the interaction effect between water and fertilizer applications on irrigated lowland rice (NSIC Rc218); to determine the relationships of other plant characters which are contributory to yield; and to assess the cost and return of irrigated lowland rice production ha-1 as influenced by water and fertilizer applications. Two methods of water application were evaluated and results showed that alternate wet and dry methods (AWD) were able to save 19.02% of the total water received by the rice plants compared to continuous flooded condition. Grain yield of irrigated lowland rice (NSIC Rc218) was significantly (p<0.05) increased by 1.84 t ha-1 which is higher by 35% when applied with recommended inorganic fertilizer at the rate of 100-60-60 kg N, P205 and K20 ha-1 (T2) than that of unfertilized plants (T1). Correlation analysis showed that grain yield is positively correlated to the number of productive tillers panicle, panicle length (cm), % filled spikelet panicle-1, weight of 1000 grains (g) and LAI but not on the number of spikelets panicle-1. Plants applied with 100-60-60 kg N, P205 and K20 ha-1 (T2) and those applied with 75% RRIF + 25% RRVC (T4) generated the highest net income of PhP 66,915.00 ha-1 and PhP 60,440.00 ha-1 respectively, than unfertilized plants of PhP 40,375.00 ha-1.